Christian Tithe vis-a-vis Islamic Zakat Concept: A Comparative Study in Socio-Economic Scope - Dawam, Khaerud; Ibrahim, Muhammad Yusuf; As-Salafiyah, Aisyah; Lubis, Rusdi Hamka (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
This study is aim to compare a social fund concept in Islam and Christian. Comparing a tithe as an instrumen of christian social funds and zakatas an instrument of Islamic social funds. Moreover, this study will delve a scheme of eachconcepts and compare its effeciency in achieve a socio- economic goals. The study was applied a dual qualitative methods. The first is literature review method, which is use to identify a relevant theories of a study. Theories will be compared by a second method, that is, qualitative comparativeanalysis method. The findings is, tithe and zakat has same objectives, that is, a human prosperity. But, both ofthese differences in collecting and distribution procedure. A titheis collected of 10% froma congregation when he gets sustenance. And the distribution is left to the church for any purpose. Meanwhile, a total collection fund of zakat is only2.5%per Muslim. Then, it’s only obligated to a man who meet requirement. Distribution concept that was regulated in Islamic scripture (Qur’an)f. The research was only compare a tithe and zakat instruments as a representation ofIslamand Christian social funds. And the study was only a theoriticalresearch. That is limited in Islam and Christian in social- economic views. The study inspired by two previous studies, that is, Dahl & Ransom(1999) and the study of Ahmad & Mahmood(2009). Researcher hasn’t found a study as like as this study yet. So, it can be stated that it was an original study.